IMPLEMENTASI PEMBIASAAN MEMBACA SURAH-SURAH AL-QUR’AN DALAM MEMBENTUK KARAKTER SPIRITUAL SISWA DI SMA 45 PURWODADI - Sultonul Hakim; Muhammada; Saifulah; Muhammad Nur Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of habituation in reading selected Qur’anic surahs to develop students’ spiritual character at SMA 45 Purwodadi. This research uses a descriptive qualitative approach based on Creswell’s theory, with the researcher acting as the main instrument. Data were collected through observation, interviews, and documentation, involving students, Islamic Education teachers, the principal, and homeroom teachers as participants. The results show that the habituation program is carried out systematically and continuously every morning before learning activities, creating a religious school culture. The practice of reading Surah Al-Waqi’ah, Al-Mulk, and Yasin contributes positively to improving students’ religiosity, discipline, emotional control, and moral behavior. Although some obstacles were found, such as low student motivation and the influence of excessive gadget use, the program remains effective in shaping students’ spiritual character. Continuous evaluation and collaboration between teachers, schools, and parents are needed to optimize the program outcomes.